Association between butyrylcholinesterase and cerebrospinal fluid biomarkers in Alzheimer's disease patients. (22nd February 2017) - Gabriel, António José; Almeida, Maria Rosário; Ribeiro, Maria Helena; Durães, João; Tábuas-Pereira, Miguel; Pinheiro, Ana Cristina; Pascoal, Rui; Santana, Isabel; Baldeiras, Inês
Highlights: 217 AD patients and 200 controls were genotyped for ApoE and BuChE-K variant. CSF BuChE activity, Aβ42, t-tau and p-tau levels were determined in 88 AD patients. BuChE-K did not seem to confer risk for AD or influence BuChE activity in CSF. CSF BuChE activity correlated with Aβ42 levels, particularly in AD ApoE-ε4 carriers. Abstract: The deficit of cholinergic activity is one of the main findings in Alzheimer's disease (AD), and is related to the synthesis of acetylcholine, and the hydrolysing enzymes, acetylcholinesterase and butyrylcholinesterase (BuChE). Together with the Apolipoprotein E-ε4 allele (ApoE-ε4), the BuChE-K variant has been proposed to increase AD risk in certain populations. In addition, this polymorphism has been associated with a lower capacity to attenuate β-amyloid aggregation. In the present study we explored the interaction of the BuChE-K variant with its activity in CSF, conventional AD biomarkers and ApoE genotype. 217 AD patients and 200 age-matched controls were genotyped for the ApoE and the BuChE-K variant. BuChE activity in CSF, as well as the levels of the CSF-AD biomarkers amyloid-beta 42 (Aβ42), total and hyperphosphorylated tau (t-tau and p-tau) were determined in 88 of these patients. The results showed no significant differences in the BuChE-K variant distribution between patients and controls. No influence of the BuChE-K variant was seen neither in CSF BuChE activity, nor in the levels of Aβ42, t-tau and p-tau in AD patients. ApoE genotype also did not seem to influence CSF BuChE activity. Interestingly, in AD patients, an association between high CSF BuChE activity and increased levels of CSF Aβ42 was shown, particularly in ApoE-ε4 allele carriers. In our population, the BuChE-K variant does not seem to confer risk for AD or to influence the activity of the enzyme in CSF. However, we demonstrated an association between BuChE activity, ApoE-ε4 genotype and CSF Aβ42 levels, highlighting the importance of assessing BuChE activity as a possible modulator of Aβ load in the brain.